Development of Blast Resistant Lines using marker assisted selection - Sharma, T. R.; Singh, A. K.; Rathour, Rajeev; Variar, M.; Prashanthi, S. K. (Indian Farming, 2015)
A typical gene-for-gene system is adopted in rice blast resistance, in which interaction between resistance gene (here Pi54) and its corresponding AVR gene (AvrL Pi54) from the pathogen results in resistance response in the host. An attempt to identify probable candidates of the avirulent counterpart of Pi54 gene, in silico genome wide analysis of M. oryzae genome sequence was performed. The Avr: Pi54 gene could be used in R-Avr two components system to develop broad spectrum resistance against rice blast disease.